Nutritional Status of Primary School Children in Kintamani, Bangli, Bali Based on School Screening Program - Cintya Riska Prathiwi Ni Ketut; Sutadarma I Wayan Gede (Epidemiology and Society Health Review (ESHR), 2026)
Background: Bangli regency has the highest prevalence of stunting in Bali with 43.2% children under 5 years old is stunting. However, nutritional status among school age children here has not been reported in any studies. The aim of this study is to determine the nutritional status of primary school children in Kintamani, Bangli. Method: This study was a descriptive cross-sectional study which conducted alongside school screening programs in 9 primary schools. Nutritional status of children aged 6-13 years was assessed based on body mass index, weight and height for age and gender according to the references from WHO. Results: Out of 1,158 children participated, 602 (52.0%) were male and 556 (48.0%) were female. The prevalence of severe thinness, thinness, overweight, and obesity are 0.3%, 1.2%, 71.6%, 15.9%, 11.0%, respectively. The prevalence of stunting among primary school age children (HAZ<2) was 9.3%. The proportion of children with nutritional problems (both under and overnutrition) were higher in male than female. This study showed that other than undernutrition, overnutrition such as overweight and obesity in older children is increasing and the trend were also found in other countries, possibly due to lack of physical activity, micronutrient deficiencies, and unhealthy diet. Therefore, evidence-based interventions are needed for all children with nutritional problems. Conclusion: Double burden of malnutrition was found in Kintamani, Bangli, Bali. The higher prevalence of overnutrition among school aged children should be highlighted and concerned as important as undernutrition mattered.